Hydrogels: Hydrogel Retaining Toxin‐Absorbing Nanosponges for Local Treatment of Methicillin‐Resistant Staphylococcus aureus Infection (Adv. Mater. 22/2015). (June 2015) - Wang, Fei; Gao, Weiwei; Thamphiwatana, Soracha; Luk, Brian T.; Angsantikul, Pavimol; Zhang, Qiangzhe; Hu, Che‐Ming J.; Fang, Ronnie H.; Copp, Jonathan A.; Pornpattananangkul, Dissaya; Lu, Weiyue; Zhang, Liangfang
<x xml:space="preserve">Abstract</x> On page 3437, L. Zhang and co‐workers describe a hybrid nanomaterial, integrating unique toxin‐absorbing nanosponges with hydrogels, that is developed for local anti‐virulence therapy against methicillin‐resistant Staphylococcus aureus (MRSA) infection. The hydrogel effectively retains the toxic nanosponges post administration without compromising toxin transport into the gel for neutralization. The nanosponge–hydrogel hybrid markedly reduces MRSA skin lesion development in a mouse model.